A Technoeconomic Model Coupled with HYSYS to Analyze the Electroreduction of Carbon Dioxide to Ethanol. Issue 4 (12th February 2023) - Pickett, Isabelle; Vo, Trang (Tracy); Wu, Ho Yan; Expósito, Antonio José
Abstract: This research develops a technoeconomic analysis to study the profitability of ethanol production from CO2 electroreduction. A HYSYS simulation is used to calculate the separation costs, a challenge in previous models available in literature. The profitability of a 10 000 kg per day CO2 electroreduction plant to produce ethanol is studied. An optimization of the pressure swing adsorber and distillation tower, which greatly influence the total cost of the plant (≈20% of total cost), is carried out, obtaining a total cost of separation of £1.94 × $\ × \ $ 10 6 . The study demonstrates that reducing the voltage applied to values around 0.5 V, i.e., by increasing the pH up to 12 makes the process economically feasible with a current density over 15 mA cm −2 . It also shows that the process is economically feasible using a current density of 5 mA cm −2 if the electricity cost from renewable sources drops to 2.0 × $\ × \ $ 10 −2 £ kWh −1 . Finally, it is proved that if catalyst stability is not considered, some catalysts currently available in the literature can be used with a positive economic income. The results of this research show that the industrial electroreduction of ethanol can be feasible and can attract interest in the industrial adoption of the technology. Abstract : The synthesis of ethanol from CO2 electroreduction is a potential technology to produce green fuels. The profit of a plant to treat 10 000 kg CO2 per day is investigated. HYSYS simulations are used to accurately calculate the cost of product separation. It is concluded that existing catalysts can be profitable with the current renewable electricity cost of 2.0 × $\ × \ $ 10 −2 £ kWh −1 .